2021
DOI: 10.1002/pds.5349
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of high‐risk prescription opioid use in the United States, 2011–2016

Abstract: Purpose: Despite the efforts of many stakeholders to reduce the risk of opioid overdose, there is limited information on the prevalence of high-risk prescription opioid use in the US.Methods: Descriptive analysis of a nationally representative 5% random sample of anonymized, longitudinal, individual-level prescription claims from IQVIA LRx between January 1, 2011 and December 31, 2016 among individuals ages 18 years or older that used a retail pharmacy. High-risk opioid use was defined as ≥50 morphine milligra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…It is notable that the largest rates of benzodiazepine prescribing occurred in the southern and western parts of the country. This finding is consistent with previous literature that found that changes in high-risk prevalence for opioid and benzodiazepine co-prescribing over the years have been greatest in the southern and western regions of the United States 20 . Given that our study did not identify a significant decrease in prescribing, continued efforts to reduce prescribing should be focused on these regions.…”
Section: Discussionsupporting
confidence: 92%
“…It is notable that the largest rates of benzodiazepine prescribing occurred in the southern and western parts of the country. This finding is consistent with previous literature that found that changes in high-risk prevalence for opioid and benzodiazepine co-prescribing over the years have been greatest in the southern and western regions of the United States 20 . Given that our study did not identify a significant decrease in prescribing, continued efforts to reduce prescribing should be focused on these regions.…”
Section: Discussionsupporting
confidence: 92%
“…Recent literature has often compared factors related to opioid overdose in younger versus older populations [ 29 ]. However, research focused within the older population is limited.…”
Section: Introductionmentioning
confidence: 99%